Dominasi Dan Perlawanan Dalam Novel Qolbu Al Lail Karya Naguib Mahfouz (Analisis Wacana Kritis) - Syah, Abdulloh Jalaluddin; Rahtikawati, Yayan; Suprianto, Ade Ahmad (STIQ Amuntai, 2025)
Novel is one type of literary work that has the function of being a mirror of the social, cultural, and political life of society. This research aims to describe the textual level, discourse level, and sociocultural level that show various practices of domination and resistance in the novel Qolbu Al-Lail. This research uses a descriptive-analytic qualitative approach. The data source of this research is the novel Qolbu Al-Lail by Naguib Mahfouz. The data obtained is analyzed using Norman fairclough's critical discourse analysis theory. The theoretical foundation used is Pierre Bourdieu's symbolic domination theory. Based on the research, the following two things are known. The critical discourse analysis of this novel reveals the existence of symbolic domination and resistance reflected in 1) the textual level (diction, grammatical structure, language style), 2) the level of discourse practice (criticism of the Egyptian political and social system after the 1952 revolution), and 3) the sociocultural level (Egyptian social conditions in 1952-1975).